2017
DOI: 10.1080/09513590.2017.1318274
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of IVF cycles coupled with PGS by aCGH of embryos from donor and autologous oocytes, transferred after vitrification to women of advanced maternal age

Abstract: It is well documented that aneuploidy rate in preimplantation embryos increases with the mother's age, and at the same time the number of oocytes diminishes. Consequently, for patients of advanced maternal age two options are available to overcome these limitations: use of oocytes from young donors, or use of own oocytes coupled with preimplantation genetic screening (PGS) for 24 chromosomes. However, it is not clear which strategy might be more effective. The aim of this retrospective study was to evaluate ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Fedorova et al evaluated the use of PGT-A via aCGH in patients with advanced maternal age who utilized either autologous or donor oocytes. 9 They expectedly found that non-PGT-A autologous cycles had higher miscarriage rates than non-PGT-A OD cycles, with the latter group presenting an SABR of 21%. Limitations were that the ages of the donors were not discussed and delivery rates were not available.…”
Section: Discussionmentioning
confidence: 96%
“…Fedorova et al evaluated the use of PGT-A via aCGH in patients with advanced maternal age who utilized either autologous or donor oocytes. 9 They expectedly found that non-PGT-A autologous cycles had higher miscarriage rates than non-PGT-A OD cycles, with the latter group presenting an SABR of 21%. Limitations were that the ages of the donors were not discussed and delivery rates were not available.…”
Section: Discussionmentioning
confidence: 96%
“…Even young oocyte donors may produce significant rates of chromosomally abnormal embryos. An unexpectantly wide range of chromosomal abnormalities in embryos derived from young oocyte donors (average age, 24-27.8 years) has been reported by several studies (18%-61%) (20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 96%
“…Whether this higher than expected prevalence is related to advanced paternal age of the recipients is still uncertain. Although OD represents a good model to address this question by enabling a control for maternal age, the existing literature regarding the effect of paternal age on embryo aneuploidy in embryos derived from OD is limited, and the specific paternal age effect remains a subject of controversy (19,(26)(27)(28)(29)(30). Moreover, literature on associations between paternal age and specific types of aberrations, including segmental and complex aberrations, in egg donor cycles, is scarce.…”
mentioning
confidence: 99%
“…Theoretically, the transfer of euploid embryos would increase the implantation rate and live birth rate. However, the efficacy of PGT-A in patients with advanced maternal age is still debated (23)(24)(25). Moayeri suggested that PGT-A could be recommended as a screening method for all patients of advanced maternal age.…”
Section: Discussionmentioning
confidence: 99%
“…et al(23) held that the regular use of PGT-A in advanced maternal age should not be recommended. However, Elena et al(24) …”
mentioning
confidence: 97%